First complete mitochondrial genome of the Alashan ground squirrel (Spermophilus alashanicus) (Rodentia: Sciuridae) from Ningxia, China - Yao Zhao; Jun Liang; Jingyao Li; Zhirong Zhang; Yue Sun; Fubin Liu; Xu Zhang; Yongliang Liang; Liwei Teng; Zhensheng Liu (Mitochondrial DNA. Part B. Resources, 2024)
AbstractThe Alashan ground squirrel (Spermophilus alashanicus) is primarily distributed in the regions of Inner Mongolia and Ningxia, China. In this study, we present the first complete mitochondrial genome of S. alashanicus. The genome spans 16,464 base pairs and comprises 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and a single control region with a marked AT bias. The overall GC content is 35.4%. Phylogenetic analyses indicate that S. alashanicus clusters are closely associated with S. dauricus. This comprehensive characterization of the S. alashanicus mitochondrial genome serves as a foundational resource for future studies on mitochondrial evolution, species identification, population genomics, and phylogenetics.